VALHUDES: A protocol for validation of human papillomavirus assays and collection devices for HPV testing on self-samples and urine samples - Arbyn, M.; Peeters, E.; Benoy, I.; Vanden Broeck, D.; Bogers, J.; De Sutter, P.; Donders, G.; Tjalma, W.; Weyers, S.; Cuschieri, K.; Poljak, M.; Bonde, J.; et al. (Journal of clinical virology, 2018)
•VALHUDES is a protocol for validation of HPV tests applied on vaginal self-samples and urine specimen.•VALHUDES will generate the first clinical data regarding the accuracy of HPV tests on vaginal & urine samples.•VALHUDES will generate comparative data sets for different combinations of HPV test and self-sample devices.•VALHUDES will contribute in defining validation criteria for HPV tests on self-samples. Systematic reviews have concluded that hrHPV DNA testing using target-amplification tests is as accurate on vaginal self-samples as on clinician-taken specimens for the detection of cervical precancer. However, insufficient evidence is available for specific HPV assay/self-sample device combinations. The VALHUDES protocol is designed as a diagnostic test accuracy study that aims to compare the clinical sensitivity and specificity of particular hrHPV assay(s) on vaginal self-samples and first-void-urine, collected in agreement with standardized protocols, with hrHPV testing on matched clinician-taken samples. Five hundred enrolled women referred to a colposcopy clinic are invited to collect a first-void urine sample and one or more vaginal self-samples with particular devices before collection of a cervical sample by a clinician. Sample sets are subsequently analysed in a laboratory accredited for HPV testing. Disease verification for all enrolled patients is provided by colposcopy combined with histological assessment of biopsies. A first VALHUDES study has started in Belgium in December 2017 with enrolment from four colposcopy centres. The following assays are foreseen to be evaluated: RealTime High Risk HPV assay (Abbott), cobas-4800 and -6800 (Roche), Onclarity (BD), Xpert HPV (Cepheid) and Anyplex II HPV HR (Seegene). Given empirical evidence that the relative accuracy of HPV-testing on self- vs clinician-samples is robust across clinical settings, the VALHUDES protocol offers a framework for validation of HPV assay/self-sample device combinations that can be translated to a primary screening setting.